Analytical circuit model for split ring resonators in the far infrared and optical frequency range - Delgado, V.; Sydoruk, Oleksiy; Tatartschuk, Eugen; Marqués, R.; Freire, M. J.; Jelinek, L. (Metamaterials, 2009)
The article proposes an LC-circuit model for single split ring resonators (SRRs) operating at far infrared and optical frequencies. Taking the effects of magnetic and kinetic inductances as well as gap and surface capacitances into account, we obtain analytical expressions for the resonant frequency of the singly, doubly, and quadruply split SRRs. Comparing the analytical results with numerical simulations, we show that the numerical simulations agree better with the present model than with the models reported previously. We also discuss a size dependent correction to the electron collision frequency which takes into account electron collisions with SRR walls.
EAM Import::2019-03-13

Analytical formulation for the resonant frequency of split rings - Sydoruk, Oleksiy; Tatartschuk, Eugen; Shamonina, E.; Solymar, L. (Journal of Applied Physics, 2009)
A simple approximate expression is derived for the resonant frequency of a singly split single ring that is among the first microwave resonators designed to be small relative to the wavelength. In addition to the usual gap capacitance the concept of surface capacitance is introduced. The surface capacitance is determined analytically by two different methods, first using analytical expressions for the electric field of a split cylinder, and second by using conformal mapping. Taking two practical examples the resonant frequency, found analytically, is shown to agree with that obtained by numerical simulations. The model could be used for studies of the resonant properties of split rings in the terahertz region.
EAM Import::2019-03-13

Generalized Brillouin diagrams for evanescent waves in metamaterials with interelement coupling - Tatartschuk, Eugen; Radkovskaya, A.; Shamonina, E.; Solymar, L. (Physical Review B, 2010)
A graphical representation for two-dimensional periodic structures is introduced that provides the full information contained in the dispersion equation: not only for the pass band but for the neighboring stop bands as well. It is a seamless natural extension of Brillouin diagrams obtained by adding eight new zones which incorporate the properties of evanescent waves. The accuracy of the infinite lattice approximation is tested both by simulations and experiments using magnetoinductive waves. For waves propagating in one direction and evanescent in the other direction, the results of the three different methods are shown to be in good agreement. The versatility of the new representation and its applicability to the design of near-field manipulating metamaterials is discussed.
EAM Import::2019-03-13

Interacting waves on chains of split-ring resonators in the presence of retardation - Lomanets, Vadym; Zhuromskyy, Oleksandr; Onishchukov, Georgy; Sydoruk, Oleksiy; Tatartschuk, Eugen; Shamonina, E.; Leuchs, Gerd; Peschel, Ulf (Applied Physics Letters, 2010)
Wave propagation is studied experimentally in a one-dimensional periodic chain of magnetically coupled split-ring resonators with a spacing of about one tenth of the resonant wavelength. Retardation leads to a strong interaction between magnetoinductive and free-space waves. Two kinds of guided modes are observed: a slow backward wave which propagates far outside the light cone, and a fast forward wave close to the light cone. The two merge in a region of zero group velocity. The results are relevant for all one- and two-dimensional periodic systems interacting with waves of the surrounding space.
EAM Import::2019-03-13

Plasmonic excitations in metallic nanoparticles: Resonances, dispersion characteristics and near-field patterns - Tatartschuk, Eugen; Shamonina, Ekaterina; Solymar, Laszlo (Optics Express, 2009)
Metamaterials acquire their functionality from the structuring of the small building blocks, ``artificial atoms''. Our paper provides a study of the resonant behaviour for a variety of metallic nanoparticles in the region of hundreds of THz. Resonant modes for nanorods of rectangular cross section are investigated numerically for different types of excitation and the set of resonant frequencies (fundamental and higher order) are determined for rods of various length. From that the dispersion relationship for surface plasmon-polaritons propagating along the rod is deduced. We analyse resonant-mode near-field distribution of the electric field, including the field lines, to emphasise the underlying physics. Resonant frequencies are also found and field distributions analysed when the rods are combined to form particles of L, U and O shapes. The similarities and differences between those particles, both in the values and in the number of resonances, are discussed. The results of this study may aid the design of nanostructured metamaterials with required properties in the IR and optical domain.
EAM Import::2019-03-12